Advancing athlete development: how percentile comparison methods can identify youth developmental profiles (PCMs) - Abbott, S.; Hogan, C.; Postiglione, G.; Barclay, G.; Cobley, S. (Journal of Science and Medicine in Sport, 2024)
Objectives Inter-individual developmental differences confound the capability to accurately evaluate youth athletic performance, highlighting the need for considerate methodology and analytical approaches. The present study demonstrated how Percentile Comparison Methods (PCMs) were developed, tested, and applied to identify athlete developmental profiles in Australian youth swimming.